Chitosan Loses Innate Beneficial Properties after Being Dissolved in Acetic Acid: Supported by Detailed Molecular Modeling - Bilican, Ismail; Pekdemir, Sami; Onses, M. Serdar; Akyuz, Lalehan; Altuner, Ergin Murat; Koc-Bilican, Behlul; Zang, Lian-Sheng; Mujtaba, Muhammad; Mulerčikas, Povilas; Kaya, Murat (American Chemical Society (ACS), 2020)
Chitosan, which is obtained via deacetylation of chitin, has a variety of uses in agriculture, food, medicine, pharmaceuticals, and cosmetics. Industrial chitosan is in a gel form, which is produced by dissolving in acetic acids. These gels can be chitosan-only films or composite films that include other ingredients such as plant extracts or other polymers. Chitosan-based films, however, are not as natural as chitosan dissolved in weak acids, and they lack some of chitosan's innate properties. In this study, natural chitosan films (NCFs) were obtained from the pupa shells of black soldier flies through a process that maintains the original structure. The semisynthetic film (SCF) was then produced by dissolving the same NCF in acetic acid along with glycerol and glutaraldehyde. The semisynthetic film remarkably lost the beneficial properties of the natural film. The deteriorated characteristics include hydrophobicity, crystallinity, thermal properties, as well as a loss of fibril structure and a reduction in bacterial attachment. Moreover, the Ag-deposited NCFs manifested strikingly higher surface-enhanced Raman scattering activity as compared with the semisynthetic ones. These results, including the molecular modeling data, demonstrate that dissolving chitosan in acetic acid changes its polymeric structure.
Keywords: Black soldier fly; SERS; Synthetic; Chitosan Film; black soldier fly; synthetic; Natural; Chitosan film; chitosan film; Black Soldier Fly; natural; 3. Good health